2000
DOI: 10.1021/jo000221n
|View full text |Cite
|
Sign up to set email alerts
|

20-O-Acylcamptothecin Derivatives:  Evidence for Lactone Stabilization

Abstract: Convincing UV and NMR spectrophotometric evidence is presented which demonstrates that at physiological pH, 7.4, 20-O-acyl derivatives of camptothecin (CPT) are substantially more stable in the lactone form than the 20-OH parent. Additionally, it was determined by HPLC analysis that the lactone ring of a 20-O-ether derivative of CPT underwent endocyclic ring opening at pH > or =8.5, while the lactone ring of 20-O-acyl CPT derivatives remained unaffected. PEG (and other smaller alkyl) 20-O-acyl-CPT derivatives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
117
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(121 citation statements)
references
References 23 publications
4
117
0
Order By: Relevance
“…An additional benefit of CPT conjugation is stabilization of the active lactone form to higher pH values (19). Conjugate concentrations in Table 1 and future discussions refer to the free drug equivalent concentration of the conjugate.…”
Section: Resultsmentioning
confidence: 99%
“…An additional benefit of CPT conjugation is stabilization of the active lactone form to higher pH values (19). Conjugate concentrations in Table 1 and future discussions refer to the free drug equivalent concentration of the conjugate.…”
Section: Resultsmentioning
confidence: 99%
“…Studies with irinotecan have shown the carboxylate form of SN-38 is only 10% as potent as the lactone form (49). The CL2A-linked SN-38 is derivatized at the 20-hydroxyl position, a process that stabilizes the lactone group in camptothecins under physiologic conditions (50). Because the in vitro stability studies and the analysis of serum stability were conducted under acidic conditions, we do not have a direct measure of the carboxylate form of SN-38 in either of these conjugates, but it is reasonable to suspect that destabilization of the lactone ring could have contributed to CL2E's diminished efficacy in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Acylation of the (O20) lactone ring hydroxyl significantly increases the stability. 3,4 Hydrophilization of the CPT molecule results in water soluble forms, e.g., Irinotecan (CPT-11). The latter is the most widely used soluble prodrug, which (as well as other CPT prodrugs) requires endoplasmic activation, mainly in the liver, for conversion into the active form (SN38 5 ).…”
Section: Introductionmentioning
confidence: 99%